Interference coupling cooperative suppression method for wideband carrier communication based on improved variational mode decomposition - Dandan DONG; Ning SUN (Dianxin kexue)
The interference coupling of power line broadband carrier communication aggravates the frequency domain tailing between subcarriers, reduces the sensitivity of suppression methods, and the communication quality is poor.Therefore, a cooperative suppression method of interference coupling of power line broadband carrier communication based on improved variational modal decomposition was proposed.Based on the channel characteristics of power line broadband carrier communication, a communication channel model with multipath propagation and Doppler effect was established, the communication signal was simulated, the original signal was preprocessed by using the improved variational modal decomposition algorithm, and the suppression problem was transformed into a variational problem.At the same time, the signal was expressed in the discrete form of unconstrained variational problem.The variational problem was continuously updated to complete the separation and processing of the signal, and realize the cooperative suppression of communication interference.The experimental results show that the proposed method has low bit error rate, small frequency offset, and practical application value.